Utilizing clinical pharmacology in the drug repurposing arena: a look into COVID-19. Issue 10 (3rd October 2022) - Ruggiero, Rosanna; Balzano, Nunzia; Di Napoli, Raffaella; Sullo, Maria Giuseppa; Rossi, Francesco; Capuano, Annalisa; Rafaniello, Concetta
ABSTRACT: Introduction: Drug repurposing represented an important contribution in the management of COVID-19, becoming the first line of defense to mitigate the effects of the new coronavirus. In a brief time, drug repurposing (DR) provided potentially effective and already available drugs for COVID-19, while specific therapies against SARS-CoV-2 and/or vaccines were developing. Identifying repurposed drugs requires a multidisciplinary approach, where clinical pharmacology represents the missing piece of the puzzle. Areas covered: Nowadays, clinical pharmacology is recognized as a discipline at the core of translational science, whose activities lead to the identification of the right drug for the right patient. In the context of the COVID-19 pandemic, its role in drug development and therapy choice has been decisive and itself repositioned. In this review, we tried to highlight the important role of clinical pharmacology in the identification and evaluation of possible repurposed drugs for COVID-19. Expert opinion: We believe that clinical pharmacology had an important role in identifying patient-oriented therapy during the COVID-19 pandemic. In this context, DR was just one of the challenges for clinical pharmacology, which proved that this discipline is ready to respond to future threats.